2022
DOI: 10.35772/ghm.2022.01031
|View full text |Cite
|
Sign up to set email alerts
|

The patient-centered diabetes management during the COVID-19 pandemic

Abstract: Since December 2019, in the fight against the coronavirus disease 2019 (COVID-19) pandemic, we observed that glycemic control in people with diabetes is easily affected by lifestyle changes. To maintain a good health condition, a patient-centered approach with mental support and close monitoring is required. For these, telemedicine and online continuous glucose monitoring (CGM), are effective systems. Therefore, based on our experience during the two-year period, we reviewed the literature for appropriate acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the use of glucocorticoid therapy may exacerbate hyperglycemia once severe infections such as COVID-19 pneumonia have developed. Consequently, a study has suggested that a system that integrates telemedicine and continuous glucose monitoring (CGM) can effectively manage blood glucose levels and prevent adverse outcomes ( 23 , 24 ). As a result, CGM has gained increasing adoption in clinical settings, with a peak in related research output in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of glucocorticoid therapy may exacerbate hyperglycemia once severe infections such as COVID-19 pneumonia have developed. Consequently, a study has suggested that a system that integrates telemedicine and continuous glucose monitoring (CGM) can effectively manage blood glucose levels and prevent adverse outcomes ( 23 , 24 ). As a result, CGM has gained increasing adoption in clinical settings, with a peak in related research output in 2021.…”
Section: Discussionmentioning
confidence: 99%